SISTEM PENGONTROLAN KONDISI UDARA PADA ALAT PENGERING TERKENDALI - Manalu, Lamhot P. (Jurnal Dinamika Penelitian Industri, 2010)
A microprocessor-based laboratory dryer system was constructed to control experimental conditions in the study of the moisture content of agricultural products and medicinal plants (simplicia). The equipment also recorder the condition of the air and the sample weights during the thin-layer drying tests for these products. This paper describes the hardware and software which were developed for use in the study of drying properties of various products. Two condition process variables are controlled simulataneously: the humidity and temperature of the air in drying chamber with temperature accuracy of Â± 1 oC and relative humidity accuracy of Â± 2%. The drying conditions were held constant and the variation in conditions in the drying chamber was shown to have no measurable effect on the thin-layer drying process subject to requirement of ASABE standard.